Being Digital: The Disappointing Digital Broadcast Policy in the US - Strover, Sharon (Javnost-The Public, 2002)
Digital broadcasting policy in the US has been ineffective in creating incentives, a market structure, or consumer interest sufficient to enable the broadcast industry to transition to digital signals. In spite of the early promises of interactivity that digital broadcasting appeared to offer, digital television now appears to be condensed into services emphasising further consumer transactions. The technical standards adopted for it provided little certainty to wary manufacturers and broadcasters, digital television prices have been too high for consumers to purchase sets, set top box technology is unsettled, and consumers do not know very much about digital systems. Moreover, since cable television distributes broadcast fare to 70% of the population, that industry's carriage of digital broadcast signals is crucial, and to date, US policy has not mandated that carriage. In the meantime, cable operators have developed their own digital services to add numerous additional channels, most of which offer video-on-demand programming.